Collective and Random Fining versus Tax/Subsidy - Schemes to Regulate Non-Point Pollution: An Experimental Study - Eva Camacho Cuena; Till Requate (Kiel University, Department of Economics, 2004)
In this paper we present results of an experimental study on the performance of three mechanisms which are designed to deal with non-point source pollution : collective fining, random fining, and a tax-subsidy scheme. Our results show that collective and random fining schemes do not induce the subjects to play the efficient equilibrium. Experience from participation in similar treatments further enforces the tendency to under-abate. The taxsubsidy mechanism, by contrast, induces the efficient equilibrium action to be played more frequently than the fining mechanisms, with a slight tendency to over-abate. Experience enforces this tendency. Controlling for the subjects? risk attitude, we find that for risk averse subjects the random fining mechanism outperforms the collective fine.
Keywords: 330; Non-point source pollution; environmental policy; collective fining; random fining; tax-subsidy scheme; experiments; Umweltabgabe; Strafe; Subvention; Umweltökonomik; Experiment